Exposure to Mixtures of Pollutants in Mexican Children from Marginalized Urban Areas - Rogelio Flores-Ramírez; Francisco J. Pérez-Vázquez; Susanna E. Medellín-Garibay; Andrea Camacho Aldrete; Moisés Vallejo-Pérez; Lorena Díaz de León-Martínez; Leticia Carrizales Yáñez; Fernando Díaz-Barriga (Ubiquity Press, 2018)
Background: Exposure to contaminant mixtures in developing countries is an important public health issue. Children are identified as the most susceptible group to adverse health effects due to the exposure. Objective: The aim of this study was to conduct a screening for mixture pollutants in Mexican children in urban marginalized communities. Methods: We analyzed children (aged 6-12 years old) who resided in four urban marginalized communities in San Luis Potosi, Mexico: i) Bellas Lomas (BEL), a site with vehicular traffic; ii) Tercera Chica (TC), a site with brick kilns; Iii) Rincon de San Jose (SJR), a site with a hazardous waste landfill; and (iv) Morales (MOR) a metallurgical zone with copper-arsenic and electrolytic zinc smelters. Polycyclic Aromatic Hydrocarbons (1-hydroxypyrene (1-OHP)), benzene (trans, trans-muconic acid (t,t-MA), manganese, arsenic and fluoride were quantified in urine and lead in blood samples. Findings: Our results indicate that median exposures to manganese were 4.4, 5.2, 5.8 and 6.3 μg/L for BEL, TC, SJR and MOR, respectively. For BEL, fluoride was present at a higher concentration with 2.3 mg/L followed by MOR, TC and SJR with 1.7, 1.5 and 1.2 mg/L respectively. The highest concentrations of arsenic that were found were 11 μg/L in MOR and lead concentration was reported between 4.2 and 6.8 μg/dL, in BEL, TC and MOR. 1-OHP and t,t-MA were higher in TC (0.23 μmol/mol creatinine (cr), 429.7 μg/g cr, respectively) followed by SJR (0.09 μmol/mol cr, 427.4 μg/g cr), MOR (0.03 μmol/mol cr, 258.6 μg/g cr) and BEL (0.06 μmol/mol cr, 220.6 μg/g cr). Conclusion: Considering the large number of people, especially children, exposed to multiple pollutants, it is important to design effective intervention programs that reduce exposure and the resultant risk in the numerous urban marginalized communities in Mexico.